Pengaruh Word Of Mouth, Store Atmosphere Dan Kepuasan Konsumen Terhadap Keputusan Pembelian Pada Toko Pakaian Sipahutar Cloth Rantauprapat - Unedo Unedo; Nova Jayanti Haraha; Abd. Halim (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the effect of word of mouth, store atmosphere and consumer satisfaction on purchasing decisions at the Sipahutar Cloth Clothing Store in Rantauprapat. The research method used in this research is quantitative. In this study, the population was 42 employees of the Sipahutar Cloth Clothing Store in Rantauprapat. The research sample used saturated sampling technique by drawing the entire existing population to serve as a research sample with a total of 42 people. The data collection techniques used are observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the study prove that Word Of Mouth has a positive and significant effect on Purchasing Decisions at the Sipahutar Cloth Clothing Store in Rantauprapat. Store Atmosphere has a positive and significant effect on Purchasing Decisions at the Sipahutar Cloth Clothing Store Rantauprapat. Consumer Satisfaction has a positive and significant effect on Purchasing Decisions at the Sipahutar Cloth Clothing Store Rantauprapat. Service quality has a positive and significant effect on Purchasing Decisions at the Sipahutar Cloth Clothing Store Rantauprapat. Word Of Mouth, Store Atmosphere, Customer Satisfaction and Service Quality simultaneously have a positive and significant effect on Purchasing Decisions at Sipahutar Cloth Clothing Stores Rantauprapat. The coefficient of determination of 0.824 means that the Purchasing Decision can be explained by the Word Of Mouth variable (X1), Store Atmosphere (X2), Customer Satisfaction (X3) by 82.4%, while the remaining 17.6% can be explained by other variables not examined in this study. Keywords: Word Of Mouth, Store Atmosphere, Customer Satisfaction, Purchase Decision